India’s Reatail Sector : Perspective and Prospects (Organised and Unorganised Status) - Sharma, S. K (Journal of Commerce and Trade, 2008)
Retail is India’s largest industry accounting for over 10 percent of GDP and around 8 percent employment. Rural retail market is expected to grow by 29% to Rs.1,80,000 crore by 2010. Retailing consists of all activities involved in selling of goods and services to consumers for their personal, family or household use. The retail sector in India is highly fragmented with organized retail contributing to only 2 percent of total retail sales. Today in India we see a high rise in the purchasing power and growth of ‘middle class’ which is real consumer. The opportunities in retail industry in India will increase since Indian retailing is on the threshold of a major change. Large scale organized players are fast making in roads replacing traditional stores with modern store formats. This paper analyzes the present status of Indian retail sector in the organized as well as unorganized sectors and highlights demand drivers of retailing in India as well as the opportunities for global players. The study gives some suggestions to drive economic growth and to consolidate the gains.